Child Battering in Pakistan - SYED ZIA UD DIN, PERVAIZ ZARIF, ZAINAB PARVEEN (Journal of Fatima Jinnah Medical University, 2018)
Background: The battered baby is a global problem. It exists in developed & underdeveloped nations irrespective race, religion, occupation, socio economic status and residential area. The causes of battered baby are younger age of the parents, more than one wife, step father / mother, baby from previous husband / wife, poverty, physical / mental sickness, illiteracy and addiction of parents. This study was planned to see the trend of baby battering in Lahore, Abbottabad and Rawalpindi. Study design: Observational retrospective. Place of Study: Shahina Jamil Hospital, Abbottabad, FJMC, Ganga Ram Hospital Lahore and Fouji Foundation Hospital, Rawalpindi. Medico legal clinic, Services Hospital Lahore, Duration of study: 1st January 2012 to 31 August 2013 Material and Methods: The cases of battered baby were selected from Shahina Jamil Hospital Abbottabad Sir Ganga Ram Hospital Lahore, emergency of Services Hospital Lahore and Fouji Foundation Hospital, Rawalpindi on predesigned proforma. Results: The study showed that incidence of child battering was 38 % where parents were at the age of 15 – 20 Years and 13 % at the parental age of 51 – 60 Years. The incidence was 83 % in case of step parents and 17 % in case real parents. It was also found that the incidence of Battered Baby was 69 % in case of step baby as compared to real baby (31 %). The incidence of Battered Baby was 73 % in addict parents as compared to non addict parents (27 %). In case of mentally / physically sick parents the incidence was 63 % as compared to 37 % in case of healthy parents. In case of physically / mentally sick baby the incidence was 69 % as compared to 31 % in case of healthy babies. In lower socio economic class the incidence of Battered Baby was 57 % as compared to 32 % and 11 % in case of middle class and high gentry respectively. In laborer the incidence of Battered Baby was high (29 %) but low in babies of business men (03 %). The incidence of Battered Baby in urban area was 33 % as compared to 67 % in rural area. Conclusions & Recommendations: The incidence of cases is quite significant in our society. The trend of battered baby can be decreased by observing preventive measures such as, encouraging joint family system, treatment of physical / mental illness of parents, social / economical support, by increasing literacy rate, by conducting religious / civil rights seminars and by decreasing poverty rate.